2004
DOI: 10.3844/ajassp.2004.64.70
|View full text |Cite
|
Sign up to set email alerts
|

Information Provided by Accrual and Cash Flow Measures in Determining Firms’ Performance: Malaysian Evidence

Abstract: Accrual and cash flow measures have been argued to be able to evaluate firms' performance, although the results are inconclusive throughout countries and time. This study examined the accrual and cash flow measures independently and jointly among Malaysian firms. The study predicted that the low cash flow subgroups (high income to cash flow firms) would show better results in operating, investing and financing activities. Our descriptive analysis of the structural components of the firms seemed to confirm that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…ICR 3 and ICR 4 express the firm's capacity to pay the cost of debt, as borrowing costs (OF), using financial margins (OCF and UFCF); these ratios are classified as ICRs with a financial approach and are proposed in the article in comparison between ICRs with an economic approach. About this topic, accrual and cash flow measures have been applied to evaluate firms' performance, although the results are inconclusive throughout countries and time (Nasir and Abdullah, 2004). We suggest this analysis for verifying if the firms in the sample have significant differences between the values of ICRs calculated by applying the two different approaches.…”
Section: Ajasmentioning
confidence: 98%
“…ICR 3 and ICR 4 express the firm's capacity to pay the cost of debt, as borrowing costs (OF), using financial margins (OCF and UFCF); these ratios are classified as ICRs with a financial approach and are proposed in the article in comparison between ICRs with an economic approach. About this topic, accrual and cash flow measures have been applied to evaluate firms' performance, although the results are inconclusive throughout countries and time (Nasir and Abdullah, 2004). We suggest this analysis for verifying if the firms in the sample have significant differences between the values of ICRs calculated by applying the two different approaches.…”
Section: Ajasmentioning
confidence: 98%
“…Second, there were statistically significant differences in all ratios that make up the ratio model for the last two years before bankruptcy. (Nasir and Abdullah, 2004) sought to draw a comparison between the information provided by accrual basis and the information provided by cash of cash flows to evaluate the performance of Malaysian organizations. This study concluded that the income statement cannot alone supply information related to operating activities, investment activities and financing investments.…”
Section: Study Objectivesmentioning
confidence: 99%
“…The results indicated that an overall betterment in environmental media is achievable through a combination of various instruments-standards, license fees, subsidies and charges-along with the necessary enforcement. Murty et al (2006) for sugar industry of India, Jiang and Mckibbin (2002) for China, Goldar et al (2001) for small factories in India, Dasgupta et al (2001) for some industries in China, Hailu and Veeman (2000) for Canadian pulp and study industry and Khalid (1996) for palm oil mills in Malaysia, Bataineh (2006) for improving of competition in manufacturing companies, Salleh et al (2007) for readiness in meeting globalization challenges, Nasir and Abdullah (2004) for accrual and cash flow measures investigated the effects of economic instruments on firm's environmental performance such as the level of pollution abatement.…”
Section: Advantages and Disadvantagesmentioning
confidence: 99%